Cognitive attunement in the face of organizational plasticity. Issue 2 (13th July 2020) - Secchi, Davide
Abstract : Purpose: The paper aims to use part of the distributed cognition literature to study how employees cope with organizational plasticity, in an attempt to identify the characteristics of cognitive plasticity. Design/methodology/approach: Evidence is collected by designing and implementing an agent-based computational simulation model (the IOP 2.0) where employees have the option to use external resources and the social environment to perform tasks. As plasticity is more effective when change and uncertainty are high, the simulation features an increase in the difficulty and number of tasks to which employees need to cope. Findings: Cooperation and sharing of competence and ability are key to cognitive plasticity. Being able to master the use of some resources, together with other employees' competencies, make some achieve the most efficient task performance. Practical implications: The findings suggest that under conditions of change and plasticity, human resource management (HRM) shall attempt to develop measures to support employees' cognitive skills necessary to cope with it, for example, mostly through diagnosis, training and facilitating on-the-job dialogue. Originality/value: This is the first study that attempts a merger between organizational cognition and plasticity, and it is the first to match its results to HRM policy recommendations.